Maximizing Social Association Activities as a Place of Da’wa for Women - Hidayat, Ahmad Luthfi (Proceedings of International Conference on Da’wa and Communication, 2020)
Islam is a religion that is believed by Muslims as a religion that always calls for goodness. It is based on what has been brought and taught by the Prophet Muhammad SAW to Muslims. The presence of the Prophet among mankind as a role model and carrying a noble mission one of them is to perfect good morals. Moral problems are actually human problems from ancient times until now. To overcome these moral problems, some ulama have made their best efforts to convey messages of kindness. However, often some ulama found a little problem related to the target of the da’wah they were to convey. Da’wah is sometimes only conveyed to certain groups most of whom are male so that some of the women are still not touched by the da’wah. For this reason, many ulama try to establish a special place to convey their preaching to be more optimal. This special place is often referred to as social association (jam’iyyah). In this jam’iyyah place, there are usually many Islamic activities held where many of the women are present in order to gain a series of knowledge. That way, the religious activities contained in this jam’iyyah, In the end, it was used as a place for delivering da’wah among the targets were women. This research will describe da’wah activities for women through jam’iyyah activities. This study aims to maximize jam’iyyah activities for da’wah. This research will be conducted using a qualitative descriptive method.